Early social contact alters the community structure and functions of the faecal microbiome in suckling-growing piglets - Y.J. Bi (Elsevier, 2021)
Social contact during suckling, in an enriched social environment, can reduce the aggressive behaviours of piglets during regrouping at weaning, and improve their production performance and welfare. The aim of this study was to determine the possible impact of suckling social contact on gut microbes. We performed 16S rRNA sequencing to measure the faecal microbial structure and function in piglets experiencing social contact. Eighteen-litter piglets were allocated to two treatments: an early continuous social contact (CSC) group where piglets from adjacent pens shared a mutual pen starting at 14 days postpartum and a control (CON) group where piglets had no contact with individuals from adjacent pens during the suckling period. The piglets were regrouped at 36 days of age. The litter weights at 35 and 63 days of age were measured. Faecal samples were randomly collected at 16, 35, 42, and 63 days of age and faecal DNA was determined. The results showed that the litter weight of piglets in the CSC group was significantly decreased at 63 days compared with the CON group. Continuous social contact also significantly decreased the microbial richness at 16 and 35 days of age (P < 0.05). Firmicutes was the most abundant bacterial phylum in both groups at all detected time-points and the abundance increased with social contact. At the genus level, Lactobacillus was the most abundant bacterium after weaning and the abundance increased in the piglets with social contact. Compared with the faecal microbiota of control piglets, a total of 22 genera at 16 days, 20 genera at 35 days, 12 genera at 42 days, and 27 genera at 63 days in the faeces of CSC piglets were observed to be significantly different in abundance (linear discriminant analysis score > 3, P < 0.05). Furthermore, functional analysis of the microbial composition showed that the changes induced by early CSC mainly altered the relative abundance of metabolic and related pathways. The social contact notably had an effect on the abundance of microbial pathways for amino acid and carbohydrate metabolism. In conclusion, CSC changed the microbial composition in the faeces of piglets, which might have a negative effect on nutrient metabolism for the suckling-growing piglets. Our study provided new insight into the influence of social contact on the suckling-growing piglets.